Bail-in to End the "Too Big To Fail" Dilemma - Sunjoo Hwang (Korea Development Institute (KDI), 2017)
Designed to resolve failed banks via loss-sharing by shareholders and creditors, bail-ins were introduced to substitute bailouts, which are known to create moral hazards in banks and a crisis in national finance. However, in cases wherein the majority of creditors are the general public, governments are still more inclined to bail out, despite the bail-in instruments being available. To increase the effectiveness of bail-ins, supplementary methods, such as depositor preference and contingent convertible bonds (CoCo bonds) with rule-based triggers, are needed. - Bailouts create moral hazards, and could lead to another banking crisis. - Bail-ins resolve failed banks by sharing the burden of loss between the shareholders and creditors. - Italy's recent banking crisis shows that bail-ins can be futile. - Deposits are applied to deposits, general bonds, CoCo bonds, etc. - CoCo bonds help banks meet the regulatory capital requirements without diluting shareholders' equity, and thus, issuance volume expands rapidly. - Governments are more likely to bail out when the majority of creditors are the general public. - When the market anticipates a bailout, the government will likely choose to bail out, and vice versa. - As for 'discretionary' CoCo bonds, the government directly determines the losssharing, hence the political buren is larger. - Due to the difference in political burden, 'discretionary' CoCo bonds tend to have a lower interest rate. - A regression analysis finds that 'discretionary' CoCo bonds have a 1.72%p lower average interest rate. - Adopting depositor preference would help increase the implementability of bailing in general creditors. - Strengthening qualifications of investors in general bonds and CoCo bonds could enhance the implementability of bail-ins. - Issuing 'rule-based' CoCo bonds could enhance the implementability of bail-ins.
Keywords: 330